The Impact of Urban Planning on Places of Worship in Windhoek Namibia - KHIBA, Rita; Ntlhe, Daphne (International Journal of Environmental, Sustainability, and Social Science, 2023)
Urban planning impacts freedom of religion through planning regulations applied by local municipalities in establishing places of worship in urban areas. However, incorporating religion in urban planning in most countries has remained insignificant, regardless of the new challenges of increasing religious diversity in most cities. This paper examines the role of urban planning policies in Namibia in establishing places of worship in Windhoek and its impact on freedom of religion in the City. Data was collected by reviewing and exploring journal papers, government documents, books, and newspaper articles. Neoliberal theory was employed to guide the study. The research established that the City of Windhoek, through planning policies, has a direct impact on places of worship, and to facilitate a sustainable process, the City put a moratorium on establishing new houses of worship to reduce the number of people intending to create such facilities. Applications for even places of worship by religious bodies, including churches, are treated the same as other applications for related institutions, even though the churches and other religious facilities have different ways of worshipping. In Namibia, the government and municipal urban planning departments benefit all religious organizations equitably. The study's findings contribute to the scientific discussions on places of worship and town planning policies in developing countries. The findings will benefit all stakeholders involved in developing places of worship, such as policymakers, academics, and researchers. The study is limited to Windhoek, and further studies should incorporate both urban and rural areas.